Screening Of Malaysian Medicinal Plants For Immunomodulatory And Haemolytic Activities - Samat, Nor Azura (2003)
Twenty-six water-soluble extracts from eighteen local medicinal plant specirs and fourteen methanol extracts from ten medicinal plants were screened in order to find new immunomodulating substances from those medicinal plants. Effects on lymphocyte proliferation and macrophage function in host defense mechanism including the nitric oxide (NO) production, phagocytic activity and intracellular killing ability were tested. Lymphocyte or macrophage was treated with those extracts at the concentration of 2.5 - 50J..lg/ ml. Four of the water-soluble extracts shows mitogenicity where it causes highest mitogenicity at different concentrations. Both methanol and water-soluble extracts failed to alter or improve macrophage function neither of its phagocytic activity nor its intracellular killing ability. The water extracts of S. torvum (stem bark), C. asiatica, S. grandiflora, U. lobata (stem bark) and G. vulgaris (leaves) produce NO significantly. Apart from that, haemolyti c activity was also determined.